2017
DOI: 10.1111/hiv.12480
|View full text |Cite
|
Sign up to set email alerts
|

HIV continuum of care in Europe and Central Asia

Abstract: ObjectivesThe European Centre for Disease Prevention and Control (ECDC) supports countries to monitor progress in their response to the HIV epidemic. In line with these monitoring responsibilities, we assess how, and to what extent, the continuum of care is being measured across countries.MethodsThe ECDC sent out questionnaires to 55 countries in Europe and Central Asia in 2014. Nominated country representatives were questioned on how they defined and measured six elements of the continuum. We present our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 13 publications
4
44
0
Order By: Relevance
“…While the UNAIDS 90-90-90 document does not explicitly define a threshold, it is generally taken to be ˂1 000 copies/mL, although various thresholds have been used in different settings. [8] To assess the effect of using different thresholds and facilitate comparability across studies, we reported at multiple thresholds.…”
Section: Outcomes Suppressionmentioning
confidence: 99%
“…While the UNAIDS 90-90-90 document does not explicitly define a threshold, it is generally taken to be ˂1 000 copies/mL, although various thresholds have been used in different settings. [8] To assess the effect of using different thresholds and facilitate comparability across studies, we reported at multiple thresholds.…”
Section: Outcomes Suppressionmentioning
confidence: 99%
“…The first stage, the total number of PLHIV, is the crucial denominator against which all subsequent estimates are measured. Yet, it is often ignored or omitted because of methodological challenges in its estimation [ 7 , 8 , 20 ]. In continua in which it is included, estimation methods are diverse, with each of thirteen continua included in a recent systematic review by using a different data source and methodology to estimate this stage [ 7 ].…”
Section: Methodological Inconsistencies and Challengesmentioning
confidence: 99%
“…Unlike stage 1 which, by definition, must be estimated, subsequent stages can be directly observed given complete surveillance. As such, stage 2, the population diagnosed, is more frequently reported and definitions are more consistently applied [ 20 ]. Most frequently, all individuals ever diagnosed since the beginning of the epidemic and still alive are included, although a minority of continua apply a narrower time window and several have difficulties excluding deaths or out-migrations [ 12 , 20 ].…”
Section: Methodological Inconsistencies and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interruption of cART entails rebound of HIV viral load to infectious levels [47]. The analysis of Drews et al [48] attests the requirement of the "health care continuum" for people living with HIV [49]. High standards of awareness for "precision medicine for ART" should be followed [50].…”
Section: ) Hiv Carementioning
confidence: 99%